2023
DOI: 10.1155/2023/6661723
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Viruses in Ixodes ricinus in Europe including Novel and Potential Arboviruses

Bianca Elena Bratuleanu,
Cristian Răileanu,
Amal Bennouna
et al.

Abstract: Tick-borne pathogens are responsible for many vector-borne diseases in Europe, causing important problems for human and animal health. The composition of viral communities in ticks and their interactions with pathogens is little understood, especially in Eastern Europe, an area that represents a major hub for animal-arthropod vectors exchanges. In this study, we used metatranscriptomics to characterize the virome of 2,753 Ixodes ricinus ticks collected from France and Romania, focusing on viruses that could po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…The virus, named Norway phlebovirus 1, was detected in all six libraries and clustered together with Blacklegged tick phlebovirus 1 [ 23 ]. Similar viruses have also been detected in Belgium, France, and Bulgaria [ 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The virus, named Norway phlebovirus 1, was detected in all six libraries and clustered together with Blacklegged tick phlebovirus 1 [ 23 ]. Similar viruses have also been detected in Belgium, France, and Bulgaria [ 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 64%
“…Based on negative serological and cultural results, the authors suggested that the virus is associated with the virome of I. ricinus [24]. A similar virus was detected in France [47]. It is of interest that the closely related Yezo virus identified in 2021 in Japan is associated with febrile illness in humans [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation